Radioimmunoassay of an Early Plasmin Degradation Product of Human Fibrinogen, “Fragment A”, and its Clinical Application - Takagi, Kimiteru; Kawai, Tadashi (Thrombosis and Haemostasis, 1978)
Upon the plasmin digestion of human fibrinogen, an early cleavage product, which has been designated as fragment A, was isolated, and to study the action of plasmin in the circulation, radioimmunoassay for fragment A was carried out. This assay used rabbit immune serum obtained by injection of fragment A mixed with complete Freund’s adjuvant, and fragment A was labeled with 125I using the Chloramin-T method.In 20 normal healthy donors its serum level was 3.57 ± 1.62 μg/ml (mean ± SD), and it was increased significantly in certain diseases, such as acute leukemias, cardiovascular disorders, malignancies, renal failure, systemic lupus erythematosus and sepsis.